Necessary but Insufficient: How Educators Enact Hope for Formerly Disconnected Youth. (January 2018) - Flennaugh, Terry K.; Cooper Stein, Kristy S.; Carter Andrews, Dorinda J.
This qualitative study investigated how educators in urban second-chance high school settings made sense of their work with formerly disconnected youth. Using Duncan-Andrade's framework of critical hope, we examined how adults' orientations toward hope shaped the educational context in ways that were necessary and sufficient for student success. Findings from this study highlight the need for more critical approaches to student engagement, specifically for students most affected by systems of marginalization. Implications for urban educators and the institutions that prepare them are discussed.